Contemporary outcomes of open repair of thoracoabdominal aortic aneurysm in young patients - Johns, Neil (J Cardiothorac Surg, 2014)
BACKGROUND: Endovascular technology now permits total endovascular thoracoabdominal aortic aneurysm (TAAA) repair with high volume centres reporting encouraging results. The long-term durability of such stent grafts is unknown, leading to concerns regarding their use in younger patients. This study reports contemporary outcomes of open repair in young patients. METHODS: Outcomes for patients age 60 or younger undergoing open TAAA repair between June 1999 and August 2013 with prospective collected data were analysed retrospectively. RESULTS: Thirty-seven patients (31 men, 84%) with a median age of 56 (range 22–60) were identified with a median TAAA diameter of 6.9 cm (range 5.6-11). Aneurysm aetiology included degenerative change (18), dilation of chronic dissection (10), connective tissue disease (7) and mycotic degeneration (2). Crawford Type IV TAAA were most commonly treated (17), followed by Type II (10), Type III (7) and Type I (3). Two (5%) patients died in hospital, one from multiple organ failure and one from respiratory failure. Three patients (8%) developed temporary paraplegia, all of whom made a complete recovery and 4 (11%) patients required temporary renal replacement therapy. Median critical care stay was 5 days (range 2–28) with an in-hospital stay of 14 days (range 7–83). During a median follow-up of 72 months (range 13–171), no patient subsequently required any further aneurysm related surgical or radiological intervention. The mean (SEM) survival time was 138.5 (11) months. The 5 year survival was 79.7% (8.3) including early deaths, with no aneurysm related complications. CONCLUSIONS: The outcome of open TAAA repair in patients aged less than 60 years is favorable. It is against these results that evolving endovascular interventions must be compared. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13019-014-0195-4) contains supplementary material, which is available to authorized users.